Influence of preform preheating on dry sliding wear behavior of 304 stainless steel reinforced A356 aluminum matrix composite produced by melt infiltration casting - Gecu, Ridvan; Atapek, S. Hakan; Karaaslan, Ahmet (ELSEVIER SCI LTD, 2017)
The effect of preform preheating on wear behavior of 304 reinforced A356 matrix composite was studied. Stainless steel shavings were pressed to attain porous preforms which were infiltrated by molten A356 alloy in a subsequent process. All casting operations were performed at 730 degrees C. Preforms were inserted into mould before casting and held for varied times from 0 to 60 min. Manufactured composites were characterized by optical microscope, SEM, FEG-SEM, XRD, EDS and ball-on-disc type tribometer. Double-layered intermetallic compounds consisting of Fe4Al13 and Fe2Al5 phases were formed at interfaces, except 60 min preheated specimen. Both inadequate and excessive preform preheating adversely affected on dry sliding wear resistance while sufficient preheating led to improve tribological properties of 304 reinforced A356 matrix composite.
Keywords: Wear; Composite; Melt infiltration casting; HYBRID COMPOSITES; GRIT SIZE; AL; MICROSTRUCTURE; CARBON; Engineering